Karakteristik Kandungan Fukosantin dan Aktivitas Antioksidan Ekstrak Alga Coklat (Sargassum polycystum) pada Perlakuan Konsentrasi Pelarut Aseton dan Suhu Maserasi - Eka Wati, Ni Kadek; Suhendra, Lutfi; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): Maret, 2020)
Fucoxanthin has great potential to be developed as an antioxidant. The purpose s of this study were to determine the effect of acetone solvent concentration and maceration temperature on the fucoxanthin content and antioxidant activity of brown algae extract (Sargassum polycystum) and determine the best acetone solvent concentration and maceration temperature on the fucoxanthin content and antioxidant activity of brown algae extract (Sargassum polycystum) . The study was the experimental research which designed by using randomized block desin (RBD) with two factors. The first factor was solvent concentration that consists of 70, 80 and 90 percent. The second factor was maceration temperature that consists of 30 ±2 ?, 40 ±2 ? and 50 ±2 ?. The data were analyzed by analysis of varian (ANOVA) and continued with the Tukey test. The results showed that the concentration of acetone solvent was influential on the content of fucoxanthin and antioxidant activity but did not affect the yield. Maceration temperature is influential on yield, fucoxanthin content and antioxidant activity. Interactions between treatments of acetone solvent concentration and maceration temperature greatly affect the content of fucoxanthin and antioxidant activity but do not affect the yield. The treatment of acetone 80 percent solvent concentration and maceration temperature 30 ±2 ? is the best treatment to produce brown algae extract (Sargassum polycystum) with a yield of 3.24 ± 0.45 percent, fucoxanthin content 1.03 ± 0.01 g fukosantin/g and antioxidant activity 99 ± 8.49 ppm and show activity powerful antioxidant. Keywords: Sargassum polycystum, acetone, maceration, fucoxanthin, antioxidant.